Perancangan Tampilan Aplikasi Pembelajaran Pinandita dengan Metode Five Planes, Heuristic Evaluation, Concurrent Think Aloud, Serta Cognitive Walkthrough - Dananjaya, Made Wira Putra; Indrawan, Gede; Sariyasa, Sariyasa (JURIKOM (Jurnal Riset Komputer), 2022)
The design and development of the application display uses five areas to find out more about the needs and requirements of the user, so that it will be easy to learn and understand by the user himself. The research variables used in determining the ease of use of the application are the effectiveness and efficiency of using the application display and user satisfaction with the application display used. The sampling technique used here is purposive sampling, so the total sample used is 30 people. The research sample used is divided into 2 parts, namely, the general public and people who have an information technology educational background. The data in the study were collected by conducting interviews and questionnaires for the testing phase. Each method used is representative of the research variables. The test method used in this study is a cognitive walkthrough representing the effectiveness variable, heuristic evaluation representing the efficiency variable, and concurrent think aloud representing the user satisfaction variable.